Rebalancing meat and legume consumption: change-inducing food choice motives and associated individual characteristics in non-vegetarian adults - Anouk Reuzé; Caroline Méjean; Myriam Carrère; Lucie Sirieix; Nathalie Druesne-Pecollo; Sandrine Péneau; Mathilde Touvier; Serge Hercberg; Emmanuelle Kesse-Guyot; Benjamin Allès (BMC, 2022)
Abstract Background A shift toward more plant-based foods in diets is required to improve health and to reduce environmental impact. Little is known about food choice motives and associated characteristics of those individuals who have actually reduced their consumption of animal-based foods. The aim of this cross-sectional study was to identify change-inducing motives related to meat and legume consumptions among non-vegetarians. The association between change-inducing motives and individual characteristics was also studied. Methods This study included 25,393 non-vegetarian participants in the French NutriNet-Santé cohort (77.4% women, mean age 55.4 ± 13.9 y.). The motives related to the declared change in meat and legume consumptions (e.g., taste, environment, social pressure) were assessed by an online questionnaire in 2018. For each motive, respondents could be classified into three groups: no motive; motive, not change-inducing; change-inducing motive. Associations between change-inducing motives and individual characteristics were evaluated using multivariable polytomic logistic regressions. Characteristics of participants who rebalanced their meat and legume consumptions were also compared to those who reduced their meat but did not increase their legume consumption. Results Motives most strongly declared as having induced a change in meat or legume consumptions were health and nutrition (respectively 90.7 and 81.0% declared these motives as change-inducing for the meat reduction), physical environment (82.0% for meat reduction only) and taste preferences (77.7% for legume increase only). Other motives related to social influences, meat avoidance and meat dislike were reported by fewer individuals, but were declared as having induced changes in food consumption. Most motives that induced a meat reduction and a legume increase were more likely to be associated with specific individual characteristics, for example being a woman or highly educated for health motives. Conclusions Besides the motives reported as important, some motives less frequently felt important were declared as having induced changes in meat or legume consumptions. Change-inducing motives were reported by specific subpopulations. Public campaigns on health and sustainability could usefully develop new tools to reach populations less willing to change. Trial registrations The study was registered at ClinicalTrials.gov (NCT03335644).